10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Context Bridge-enhanced anterior cruciate ligament (ACL) repair (BEAR) is a biologically based surgical alternative to reconstruction that seeks to restore the native ligament using a bioengineered bovine collagen-based extracellular matrix scaffold saturated with autologous whole blood. This technique has generated growing interest for its potential to preserve proprioception, minimize graft morbidity, and protect long-term joint health. Evidence acquisition A scoping review was performed following Joanna Briggs Institute (JBI) guidelines. PubMed, Embase, and MEDLINE were searched systematically through June 2025 using the terms "bridge-enhanced," "ACL repair," and "BEAR." Eligible studies included preclinical animal models and human clinical investigations evaluating BEAR outcomes. Data were synthesized thematically across preclinical and clinical domains and analyzed separately within mechanistic, biomechanical, and clinical frameworks. Study design Scoping review of preclinical and clinical studies. Level of evidence Level 5. Results A total of 26 studies (6 preclinical, 20 clinical) met inclusion criteria. Preclinical investigations demonstrated that BEAR restores ligament continuity and mechanical strength comparable with that of reconstruction while reducing cartilage degeneration in large-animal models. Human trials demonstrated comparable knee stability and patient-reported outcomes relative to reconstruction at 2 years, with superior early hamstring strength. Quantitative magnetic resonance imaging studies revealed progressive ligament maturation and signal normalization over time. Long-term durability and chondroprotection in humans remain under investigation. Conclusion BEAR represents the first clinically evaluated biologic repair strategy for midsubstance ACL tears, with current evidence suggesting functional outcomes comparable with those of reconstruction while preserving native anatomy. Further high-quality, long-term studies are needed to define patient selection, optimize surgical timing, and to determine durability of biologic healing.Strength-of-Recommendation Taxonomy (SORT):Level B: consistent limited-quality patient-oriented evidence.